HIST2H2BF Potentiates the Propagation of Cancer Stem Cells via Notch Signaling to Promote Malignancy and Liver Metastasis in Colorectal Carcinoma - Qiu, Lei; Yang, Xiuwei; Wu, Jingyu; Huang, Changzhi; Miao, Yongchang; Fu, Zan (Frontiers in Oncology, 2021)
Background: Growing evidence demonstrates that the initiation and progression of colorectal carcinoma (CRC) is related to the presence of cancer stem cells (CSCs). However, the mechanism through which the stem cell features of CRC cells are maintained is poorly understood. In this study, we identified the oncogenic histone cluster 2 H2B family member F (HIST2H2BF) and aimed to investigate the function of upregulated HIST2H2BF expression in maintaining the stem cell features of CRC cells, which accelerate the progression of CRC. Methods: HIST2H2BF expression was quantified using real-time polymerase chain reaction, immunohistochemistry, and western blotting. The correlation between CpG island methylation status and HIST2H2BF re-expression was assessed through bisulfite sequencing polymerase chain reaction, methylation-specific polymerase chain reaction, and 5-Aza-dC treatment. Functional assays were performed on CRC cells and mice to investigate the HIST2H2BF-induced stem cell-like and cancer properties of CRC. Using the Notch pathway inhibitor FLI-06, the regulatory effect of HIST2H2BF on downstream Notch signaling was confirmed. Results: HIST2H2BF was highly expressed in CRC tissues and cell lines. The reactivation of HIST2H2BF in CRC stems at least in part from the hypomethylated CpG islands. CRC patients with high HIST2H2BF expression have poor survival outcomes. Functional studies have shown that HIST2H2BF promotes CSC phenotype, malignancy, and liver metastasis through the activation of Notch signaling in CRC. Blockage of the Notch pathway reduced the stem cell-like and cancer properties. Conclusion: Our study suggests that HIST2H2BF upregulation enhances the CSC phenotype, malignancy, and liver metastasis through the activation of Notch signaling in CRC. These results identified a new perspective on the mechanism by which the stem cell features of CRC cells are maintained and highlighted the potential novel therapeutic targets for CRC.